2000
DOI: 10.1046/j.1365-2214.2000.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast‐feeding and weight change in newborns in Jamaica

Abstract: This study was conducted to examine weight change of exclusively breast-fed infants during the first week and through the first 24 days of life, and to evaluate the effect of breast-feeding factors and maternal characteristics on early weight change in the infants. The weights of 21 infants were recorded on day 1 (day of birth), and on days 3, 7, 10, 17, and 24, and the data analysed to evaluate weight change over the period. Multiple regression analysis was used to assess whether birth weight as well as mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Hossain et al reported that 56% of newborns started to regain weight within the first 5 days in their studies involving low birth weight newborns [14]. Jolly et al reported that 90% started to regain weight within the first 3 days [15]. In our study, it was observed that 15.3% of all newborns started to gain weight within the first 3 days after delivery, and a total of 26% started to gain weight within the first 7 days.…”
Section: Discussionsupporting
confidence: 55%
“…Hossain et al reported that 56% of newborns started to regain weight within the first 5 days in their studies involving low birth weight newborns [14]. Jolly et al reported that 90% started to regain weight within the first 3 days [15]. In our study, it was observed that 15.3% of all newborns started to gain weight within the first 3 days after delivery, and a total of 26% started to gain weight within the first 7 days.…”
Section: Discussionsupporting
confidence: 55%
“… and Macdonald et al. weighed the newborn infants on the day of birth and then on specific days: days five and 10 ; days three, seven, 10, 17 and 24 ; and at discharge and on days five, seven, 10 and 14 , respectively. Only Martin‐Calama et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the aforementioned studies, newborn weight change was described as the amount and, or, timing and the diversity of descriptions made it even harder to compare study results. Weight change has been previously described as the amount in grams or kilograms lost or gained , as the percentage of birthweight lost or gained , or simply as the day when the newborn infants started to gain weight or when they regained their birthweight . In addition, some authors presented the results as mean weight change , median weight change , range of weight change , number of subjects over or under some predetermined percentage of weight loss or percentile data .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that a permanent contraction in extracellular fluid volume triggered by the process of birth itself causes some early weight loss. Cultural norms also influence patterns of lactation immediately after birth, and it has long been held that Caucasian babies take longer than African and Asian babies to regain their birthweight (24–27). The earliest studies to report this relied on data collected at a time when European babies born in hospital were never offered anything other than sugar water for at least the first 24 h of life (25,28), but most of the studies that have found a pattern of weight change similar to the one summarized in Figure 1 (3,29,30) have come from communities where it remains uncommon to put the baby to the breast more than once or twice on the first day of life.…”
Section: Discussionmentioning
confidence: 99%